2019
DOI: 10.23916/0020190420920
|View full text |Cite
|
Sign up to set email alerts
|

Increasing long jump performance through plyometric exercises

Abstract: Low athlete’s long jump performance and training that use are not systematic. This study aims to decide the effect of plyometric training on athlete performance. This study was a quasi-experiment comprising 32 athletes taken using a purposive sampling technique. The instrument with the long jump test is under the standard of the Indonesian Athletics Association (PASI), and the data analysis uses t-test. Based on data analysis; there were significant differences in athlete performance before and after being giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Based on the results of the study, it was found that plyometric circuit training could increase the jump power. These results were in line with the theory that plyometrics is a form of exercise that can increase power [9][10].…”
Section: Discussionsupporting
confidence: 90%
“…Based on the results of the study, it was found that plyometric circuit training could increase the jump power. These results were in line with the theory that plyometrics is a form of exercise that can increase power [9][10].…”
Section: Discussionsupporting
confidence: 90%